THE EFFECTIVENESS OF USING TIME TOKEN (TT) MODEL TO IMPROVE STUDENTS SPEAKING SKILL AT VII GRADE MTs SWASTA NURUL ISLAMACADEMIC YEARS 2023/2024 - Elvi Hilda Jayanti; SabrunJamil; Putri Ayumi (STKIP USMAN SAFRI KUTACANE, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out The Effectiveness of Using Time Token (TT) Model To Improve Student Speaking Skills at VII grade MTs Swasta Nurul Islam Academic Year 2023-2024. The population of this study consists of all 25 students in Class VII, with a sample size of 25 students. The research method employed is an experimental method with a one-group pretest and posttest design, and data analysis using the